Dosimetric integration of daily mega-voltage cone-beam CT for image-guided intensity-modulated radiotherapy - Zabel-du Bois, Angelika; Nill, Simeon; Rhein, Bernhard; Schwahofer, Andrea; Milker-Zabel, Stefanie (Strahlentherapie und Onkologie, 2012)
PurposeThe goal of this work was to compare different methods of incorporating the additional dose of mega-voltage cone-beam CT (MV-CBCT) for image-guided intensity modulated radiotherapy (IMRT) of different tumor entities.Material and methodsThe absolute dose delivered by the MV-CBCT was calculated and considered by creating a scaled IMRT plan (scIMRT) by renormalizing the clinically approved plan (orgIMRT) so that the sum with the MV-CBCT dose yields the same prescribed dose. In the other case, a newly optimized plan (optIMRT) was generated by including the dose distribution of the MV-CBCT as pre-irradiation. Both plans were compared with the orgIMRT plan and a plan where the last fraction was skipped.ResultsNo significant changes were observed regarding the 95% conformity index of the target volume. The mean dose of the organs at risk (OAR) increased by approx. 7% for the scIMRT plan and 5% for the optIMRT plan. A significant increase of the mean dose to the outline contour was observed, ranging from 3.1 ± 1.3% (optIMRT) to 13.0 ± 6.1% (scIMRT) for both methods over all entities. If the dose of daily MV-CBCT would have been ignored, the additional dose accumulated to nearly a whole treatment fraction with a general increase of approx. 10% to the OARs and approx. 4% to the target volume.ConclusionBoth methods of incorporating the additional MV-CBCT dose into the treatment plan are suitable for clinical practice. The dose distribution of the target volume could be achieved as conformal as with the orgIMRT plan, while only a moderate increase of mean dose to OAR was observed.
Gesehen am 21.08.2018